ATTRIBUTES OF MAXILLARY COMPLETE DENTURE SUPPORTING TISSUES IN SUBJECTS AT A DENTAL HOSPITAL - Ghani, Fazal; ., Faheemullah (Journal of Postgraduate Medical Institute, 2011)
Objective: To document anatomical features of maxillary edentulous denture supporting tissues (DSTs) in subjects. Material and Methods: From September 2006 to May 2007, a case-series study, involving 100 subjects having maxillary edentulous DSTs was conducted at KCD Peshawar. Using a structured proforma, data were recorded for un-favourable and favourable features of each of the anatomical structures of the DSTs including radiographic findings and need and category of pre-prosthetic surgical procedures. Results: Subjects (70 males: 30 females) had mean age 61.3±10.7SD with 34% older than 65 years. Majority (69%) subjects were poor. Caries and periodontal disease were reasons for tooth loss in 99% subjects with mean duration of edentulism in months as 19.5 + 38.3 SD). The percentages of subjects exhibiting unfavouable features for residual alveolar ridge (RAR) height and width, arch size, maxillary tuberosity, alveolar mucosa and presence of retained roots and teeth on radiographs were 47, 70, 81, 25 and 12 respectively. The percentages of subjects having unfavourable hard palate depth, arch form, soft palatal throat morphology, presence of median palatal fissure, unfavourable labial and buccal border tissue attachment levels, presence of palatal tori and unfavourable tuberosity-sinus relationship were 20, 10, 16, 6, 4, 8, 4, 56 respectively. Need for pre-prosthetic surgery was seen in 18% subjects. Chi-square analyses of data showed significant association between age and oral mucosa, gender and arch size and gender and depth of hard palate. Conclusion: The unfavourable nature of the DSTs in many subjects indicates their treatment difficulty in a general practice environment.